Effects of Low Incoming Turbulence on the Flow around a 5 : 1 Rectangular Cylinder at Non-Null-Attack Angle. (5th September 2016) - Ricci, M.; Patruno, L.; de Miranda, S.; Ubertini, F.
Abstract : The incompressible high Reynolds number flow around the rectangular cylinder with aspect ratio 5 : 1 has been extensively studied in the recent literature and became a standard benchmark in the field of bluff bodies aerodynamics. The majority of the proposed contributions focus on the simulation of the flow when a smooth inlet condition is adopted. Nevertheless, even when nominally smooth conditions are reproduced in wind tunnel tests, a low turbulence intensity is present together with environmental disturbances and model imperfections. Additionally, many turbulence models are known to be excessively dissipative in laminar-to-turbulent transition zones, generally leading to overestimation of the reattachment length. In this paper, Large Eddy Simulations are performed on a 5 : 1 rectangular cylinder at non-null-attack angle aiming at studying the sensitivity of such flow to a low level of incoming disturbances and compare the performance of standard Smagorinsky-Lilly and Kinetic Energy Transport turbulence models.